2020
DOI: 10.1038/s41467-020-17876-0
|View full text |Cite
|
Sign up to set email alerts
|

A single-cell atlas of the human substantia nigra reveals cell-specific pathways associated with neurological disorders

Abstract: We describe a human single-nuclei transcriptomic atlas for the substantia nigra (SN), generated by sequencing approximately 17,000 nuclei from matched cortical and SN samples. We show that the common genetic risk for Parkinson's disease (PD) is associated with dopaminergic neuron (DaN)-specific gene expression, including mitochondrial functioning, protein folding and ubiquitination pathways. We identify a distinct cell type association between PD risk and oligodendrocyte-specific gene expression. Unlike Alzhei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
232
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(282 citation statements)
references
References 38 publications
29
232
0
Order By: Relevance
“…Agarwal and colleagues 3 performed single‐cell transcriptomics of the SN and the cortex of 5 human postmortem brains and matched their data with the genetic variants contributing to 30 different human complex traits (pertaining to different categories such as autoimmune diseases, neurological disorders, and neuro‐psychiatric disorders). They found nonoverlapping associations of PD genetic risk with dopaminergic neurons, oligodendrocytes (also found in an independent study using mouse transcriptomic data 4 ), and oligodendrocyte precursor cells (OPCs), proposing distinct PD‐associated cell etiologies within the SN.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Agarwal and colleagues 3 performed single‐cell transcriptomics of the SN and the cortex of 5 human postmortem brains and matched their data with the genetic variants contributing to 30 different human complex traits (pertaining to different categories such as autoimmune diseases, neurological disorders, and neuro‐psychiatric disorders). They found nonoverlapping associations of PD genetic risk with dopaminergic neurons, oligodendrocytes (also found in an independent study using mouse transcriptomic data 4 ), and oligodendrocyte precursor cells (OPCs), proposing distinct PD‐associated cell etiologies within the SN.…”
mentioning
confidence: 99%
“…There is growing evidence that for many brain disorders, glial cells may causally contribute to neuronal alterations. Agarwal and colleagues 1 described a human single‐nuclei transcriptomic atlas for the substantia nigra (SN) and found a striking association between Parkinson's disease (PD) risk and oligodendrocyte‐specific gene expression, suggesting that oligodendrocytes could play a causal role in the disease. The authors' aim was to study cell‐type‐specific gene expression in the human SN to identify the potential contributions of the different cell types to PD and other neurological disorders because in other neurodegenerative diseases such as Alzheimer's disease (AD), the cell type associated with the genetic risk (microglia) is not the cell type directly associated with the disease symptoms (loss of neurons) 2 .…”
mentioning
confidence: 99%
“…Despite glial cells having been reported to induce deregulation in mitochondria and endoplasmic reticulum dysfunction resulting in bioenergetic and Ca 2+ homeostasis disruption [ 99 ], neuroinflammation is critical for AD since it appears to modulate the disease progression [ 100 , 101 ]. The integration of the immune system and the central nervous system was recently reviewed [ 102 ].…”
Section: General Aspects Of Mitogen-activated Protein Kinases (Mapmentioning
confidence: 99%
“…Among other functions, the key role of the microglia consists of the regulation of inflammation, synaptic connectivity, programed cell death, wiring and circuitry formation, phagocytosis of cell debris, and synaptic pruning and sculpting of postnatal neural circuits [ 110 ]. Research identified a correlation of specific expression patterns in microglia from the brain cortex and AD risk variations, indicating that neuroinflammation may have a more important role in AD than in other neuropsychiatric diseases [ 99 ]. It was revealed that inflammatory pathways are also linked to rapid cognitive decline in the mild cognitive impairment stage of AD [ 18 ].…”
Section: General Aspects Of Mitogen-activated Protein Kinases (Mapmentioning
confidence: 99%
“…Approaches that nominate enrichment in specific cell types have been useful in identifying likely genes as most tissues have heterogeneous cellular composition. Several approaches have nominated dopamine neurons (4)(5)(6)(7), which are principal cell types lost in PD, as mediators of neurodegeneration, although other studies have identified non-neuronal cells including oligodendrocytes and oligodendrocyte precursor cells (4,8) as contributing to disease risk. Such approaches rely on the presumed mechanism that non-coding variants affect gene expression, which can be inferred by mapping expression quantitative trait loci (eQTL).…”
Section: Introductionmentioning
confidence: 99%